Renal Cell Carcinoma - Cairns, Paul (2011)
Renal Cell Carcinoma (RCC) has the highest mortality rate of the genitourinary cancers and the incidence of RCC has risen steadily. If detected early, RCC is curable by surgery although a minority are at risk of recurrence. Increasing incidental detection and an ageing population has led to active surveillance as an option for patients with small renal masses. RCC is heterogeneous and comprises several histological cell types with different genetics, biology and behavior. The identification of the genes predisposing to inherited syndromes with RCC has provided much of our knowledge of the molecular basis of early sporadic RCC. Many of the oncogenes and tumor suppressor genes that are mutated leading to pathway dysregulation in RCC remain to be elucidated. Global studies of copy number, gene sequencing, gene expression, miRNA expression and gene methylation in primary RCC will lead towards this goal. The natural history of RCC indicated by candidate precursor lesions, multifocal or bilateral disease, growth rate of small renal masses under surveillance, and high risk populations provide insight into the behavior of this disease. The use of molecular markers for early detection and prognosis merits more attention with ongoing advances in omics technologies. This review focuses on early RCC, that is disease confined within the renal capsule.